Sierra Leone : Sixth Review Under the Extended Credit Facility Arrangement, Financing Assurances Review and Request for Waiver for Nonobservance of Performance Criteria-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Sierra Leone's Sixth Review Under the Extended Credit Facility (ECF) Arrangement, Financing Assurances Review, and Request for Waiver for Nonobservance of Performance Criteria. Growth is expected to reach 6.5 percent in the medium term. However, risks to the outlook are firmly to the downside. Revenues are too low to finance key infrastructure projects. Iron ore production has become moderately profitable, but there is downside risk to iron ore prices. The IMF staff supports the authorities' request for completion of the sixth (last) review of the ECF arrangement, as well as the request for a waiver for nonobservance of the continuous performance criteria on nonintroduction of multiple currency practices.